Confocal microscopy observations of electrical pre-breakdown of bi-layer elastomer dielectrics. (November 2021) - Charoen-Rajapark, Pavida; Clarke, David R.
Abstract: At high electric fields, the electrical energy stored in a soft elastomer dielectric can be comparable to the mechanical deformation energy it produces. This has led to the development of a class of electrically controlled, large strain dielectric elastomer actuators for soft robotics and energy harvesting devices. At large electric fields, the electro-mechanically induced deformation can lead to pseudo-periodic surface morphological instabilities which then grow with increasing field into stable pre-breakdown defects prior to final, irreversible electrical breakdown. Under these extremes of combined large electrical and mechanical deformations, the morphological evolution of the pre-breakdown defects has not hitherto been reported. In contrast to the filamentary breakdown of much stiffer dielectrics, fluorescence confocal microscopy reveals an array of defects that evolve through a complex, reversible series of morphologies, transitioning from axi-symmetric "pits" to "crack-like" shapes that can "twist" and deflect, and finally open to form an array of holes. The observations suggest that the transitions, from axi-symmetric pits to flat, slit-like defects and then to an array of holes, are geometric instabilities. The implications for using a soft elastomer layer to increase the dielectric breakdown of a stiffer dielectric are discussed.